a Profil Kemampuan Berpikir Kreatif Fisika Pada Siswa Kelas Xi Sma Negeri 2 Ende Tahun Pelajaran 2021/2022: physics creative thinking ability profile - Celin Bhoga; An Nisaa Al Mu'min Liu; Yasinta Embu Ika (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
The population in this study were all students of class XI MIA at SMA Negeri 2 Ende in the academic year 2021/2022, totaling 95 students, and the sample in this study were students of class XI MIA 2 totaling 31 students obtained by purposive sampling technique. Furthermore, the data collection technique used a non-test technique, namely a questionnaire. Data analysis was performed with descriptive statistics. The results showed that the overall average of students' creative thinking abilities was categorized as quite creative, namely (64.4%). In addition, there is 1 student who is in the very creative category that is equal to (3.2 %), 4 students in the creative category that is equal to (12.9 %), 24 students in the quite creative category that is equal to (77 %), 2 students with a less creative category that is equal to (6.5%) and no one is categorized as not creative from 31 students. This shows that most of the students of class XI IPA 2, their creative thinking skills are quite creative.